Improving the Students’ Speaking Ability by Applying Guided Conversation Strategy - Mariana, Ana; Jabu, Baso; Muliati, A. (Journal of Excellence in English Language Education, 2024)
This research aims to determine the improvement of students' speaking skills with guided conversation strategies. This research uses a pre-experimental method with data analysis using SPSS version 20.0. The respondents in this study consisted of 34 students from class VIII10 at UPT SPF SMP Negeri 17 Makassar. The results of this research show that guided conversation can improve students' speaking ability with an average (Mean) Post-test score of 16.38 with a standard deviation (data spread) from 2.456 to 3.201. This shows that guided conversation strategy can improve students' speaking ability. This can be seen from the results of the pre-test score which increased in the post-test results. The standard deviation value is smaller than the average value, so it can be concluded that the average value can represent all the data. The range of values on the Pre-test is 10 and on the Post-test 13. Ha is accepted and H0 is rejected. Furthermore, the description above shows that in the post-test results, there was an increase from the pre-test to the post-test. This shows that the application of guided conversation plays an important role in learning to speak.